Resource Dependence and Institutions: Determinants of College Behavior in Three Organizational Populations - Ivan Pavlyutkin (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
What is the connection between the external behavior of a college and its internal structure? This question is highly relevant because of the ongoing diversification of funding in Russian colleges: it is necessary to understand this connection in order to successfully manage colleges and to form their identities. To answer this question, the author uses two theoretical approaches: the resource"dependence approach and the new institutionalism. Both approaches assume a high significance of institutional surroundings in explaining the changes in organizations. A case study comparing state"owned technological, pedagogical, and law & economics colleges has been conducted in order to discover the differences between these populations of colleges. The study uses the following parameters: transparency for the consumer, investment policies towards teachers, and decision making practices.